Perlindungan Hak Masyarakat Hukum Adat di Sumatera Barat - Akmal, Akmal (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2008)
The objectives of this study are to identify the existence of cultural identity and communal rights of Minangkabau traditional society and to find a fixed and effective model in protecting the existence ofÂ cultural identity and communal rights. R & D approach was used in this study. The result of this study indicated that cultural identity of Minangkabau traditional society is still exist among the people that is indicated by the existence of: the structure of traditional government, traditional law territory, traditional judicature, Nagari government, authorizing of natural resources by Nagari government, and the structure of traditional community. The right of communal land in traditional society are still exist, and most of them are involved in civil law dispute. The model of protection toward cultural identity of traditional community is implemented toward traditional government, traditional law territory,Â traditional judicature, the structure of traditional government, and authorizing of natural resources, and Nagari government. There are many challanges and threats toward the existence of the communal lands both internal and external. It is recommended that government should conserve and fill the need of the cultural identity and the rights of communal lands of society through a fixed and effective model. Kata Kunci: Perlindungan, adat, hukum adat, Â masyarakat hukum adat, hak masyarakat hukum adat